ViMM - Virtual Multimodal Museum: A Manifesto and Roadmap for Europe's Digital Cultural Heritage - Ioannides, Marinos; Davies, Rob (My University, 2019)
Virtual Multimodal Museum (ViMM) is a major Coordination and Support Action across the field of Virtual Museums (VM), within the overall context of European policy and practice on Digital Cultural Heritage (DCH), funded under the Horizon 2020 programme of the European Union. A highly- expert seven (7) partner consortium, coordinated by Cyprus University of Technology (CUT) leverages the support of a unique and powerful Advisory Group, consisting of many of the Europe and the world's leading public and private sector organisations in the field, to define and support high quality policies, strategic and day-to-day decision making, the utilisation of breakthrough technological developments such as VR/AR and to nurture an evidence-based view of growth and development impacted by VM, supported by a set of case studies in culturally- rich regions of South Europe affected by economic recession. Its work is founded on building a consensual framework directly involving Europe's leading VM decision-makers and practitioners in defining and resolving existing issues spread across 7 interlinked Thematic Areas ('the 7 Ds'): Definitions -Directions - Documentation - Dimensions - Demand- Discovery - Decisions and aims to achieve wide-reaching stakeholder participation and very high visibility, the latter to be achieved through organisation of key events at policy and practitioner/ stakeholder levels, extensive use of the media, and by the introduction of an interactive and wide-reaching communication platform, deploying social media and novel approaches to enable focused debate by all interested parties, supported by access to representations of excellence and a decision-support tool for stakeholders. An initially broad and open approach is being refined to arrive at a validated Manifesto and Roadmap for Action on VM/DCH, validated at a final ViMM international conference. Measurable impacts are sought on the role and capability of DCH to meet its enormous potential in society and the economy.